The use of digital video in mobile application for the Arabic Language: A preliminary study - Alkasirah, Nurul Azni Mhd; Sanmugam, Mageswaran; Mohamad, Mariam; Razi, Nur Aadila Ahmad; Sharuddin, Noor Husna (International Journal of Research in Counseling and Education, 2022)
Supporting digital technology used in teaching and learning, video has opened a new opportunity for bringing a traditional learning environment to enhance learning.  The use of video through mobile applications has changed the methods and techniques of acquiring knowledge in the education field in almost all subjects such as language, science and mathematics. This changing technique offers innovative opportunities for both teachers and students to enhance language learning through technology. Previous literature has shown a respectable number of studies related to the use of video in mobile applications applied in various subjects, resulting in enormous advantages to the learners at school. Thus, the goal of this preliminary study is to identify the teaching and learning in Arabic language and to examine what is teachers done to increase in mastering Arabic vocabulary among students. This study also aimed to see teachers’ perception toward the use of video through mobile application in teaching and learning for Arabic language that can be used as guide developing an application product for the subject of the Arabic language. An online interview had been conducted among teachers from two different religious secondary schools in Penang for data collection. Findings showed that the teachers still use conventional teaching in class and only use the technology during online class. Most teachers agreed that the use of video through mobile applications can be used to improve learners’ language learning and it is most suitable to apply in the learning of the Arabic language for a secondary school in Malaysia.